Low opioid and opioid-free anesthesia - a review of current data - Czeremańska-Koczkodaj, Dorota; Grabek, Agata; Domańska, Anastazja (Journal of Education, Health and Sport, 2024)
Introduction: Opioids are one of the most frequently used drugs during anesthesia. Due to the side effects anesthesiologists try to limit their number during anesthesia. They use low-opioid and opioid-free anesthesia. Purpose: The purpose of this work is to present the current state of knowledge and recent reports on low-opioid and non-opioid anesthesia and their use. Materials and Methods: The search was conducted using PubMed and GoogleScholar databases. Articles were searched in English using the following keywords: "low-opioid anesthesia," "non-opioid anesthesia," "OFA," "LOA" Key words: "low-opioid anesthesia", "non-opioid anesthesia", "OFA", "LOA", "opioids". Conclusion: low-opioid anesthesia techniques are being used more and more frequently and reduce the incidence of opioid side effects: respiratory depression, postoperative nausea and vomiting. This helps ensure greater patient safety and shortens the postoperative recovery period.